Cytoskeletal and mitochondrial properties of bovine oocytes obtained by Ovum Pick‐Up: the effects of follicle stimulation and in vitro maturation. (8th July 2015) - Somfai, Tamás; Matoba, Satoko; Inaba, Yasushi; Nakai, Michiko; Imai, Kei; Nagai, Takashi; Geshi, Masaya
Abstract: Follicle stimulation by follicular stimulating hormone (FSH) is known to improve developmental competence of bovine oocytes obtained by Ovum Pick‐Up (OPU); however, the exact factors in oocytes affected by this treatment have remained unclear. We compared in vitro matured (IVM) oocytes obtained at the immature stage from cows by OPU either without or with stimulation with FSH (non‐stimulated and stimulated OPU, respectively) to those obtained by superstimulation and in vivo maturation in terms of cytoskeleton morphology, mitochondrial distribution, intracellular adenosine triphosphate (ATP) content and H2 O2 levels at the metaphase‐II stage and intracellular Ca 2+ levels after in vitro fertilization (IVF). Confocal microscopy after immunostaining revealed reduced size of the meiotic spindle, associated with increased tendencies of microfilament degradation and insufficient mitochondrial re‐distribution in non‐stimulated OPU‐derived IVM oocytes compared with those collected by stimulated OPU, which in turn resembled in vivo matured oocytes. However, there was no difference in mitochondrial functions between oocytes obtained by stimulated or non‐stimulated OPU in terms of ATP content, cytoplasmic H2 O2 levels, base Ca 2+ levels and the frequencies and amplitudes of Ca 2+ oscillations after IVF. Larger size of metaphase spindles in oocytes obtained by stimulated OPU may reflect and potentially contribute to their high developmental competence.